Nasionalisme dalam Al-Qur'an : (Analisis Kontektual Abdullah Saeed) - Najib , Faizin Ainun; Humaidi, Humaidi (Al-Insyiroh: Jurnal Studi Keislaman, 2020)
This article discusses about the identity of nationalism in Indonesia, the author's efforts to find the relationship in the Qur'an. While, the meaning of nationalism is still reaping the debate. Call it like HTI (read: history). The difference is caused there are different meanings to the Qur'an and a different understanding to the Qur'an.This study uses Abdullah Saeed's contextual theory. Abdullah Saeed offers a contextual interpretation system which includes, firstly, linguistic analysis and study of asbabu an-nuzul micro-macro. Secondly, the interpretation of scholars from generation to generation. Third, contextualization, namely nationalism in the Indonesian context.